Impact of left ventricular ejection fraction on clinical outcomes in females undergoing percutaneous coronary intervention with drug-eluting stents. (14th October 2021) - Nicolas, J; Cao, D; Giustino, G; Sartori, S; Snyder, C; Tavenier, A; Chiarito, M; Nardin, M; Pivato, C; Razuk, V; Baber, U; Windecker, S; et al.
Abstract: Background: Reduced left ventricular ejection fraction (LVEF) is associated with increased risk of adverse events among patients undergoing percutaneous coronary intervention (PCI). Due to under-enrollment of females in randomized trials, there is limited data on the impact of LVEF on post-PCI outcomes in female patients. Purpose: To evaluate the impact of varying degrees of LVEF impairment on 3-year outcomes in female patients undergoing PCI with drug-eluting stents (DES). Methods: We pooled patient-level data of female patients from 26 randomized trials of coronary stents. The study population was stratified into three groups according to the 2016 European Society of Cardiology Heart Failure guidelines: LVEF ≥50% (normal), LVEF 40–49% (mid-range), and LVEF <40% (reduced). The primary outcome was major adverse cardiac events (MACE), a composite of cardiac death, myocardial infarction (MI), or stent thrombosis (ST) at 3-year follow-up. The Kaplan-Meier method was used for time-to-event analyses, with comparative risks being assessed using Cox regression. Results: Out of 5672 female patients with available LVEF values at baseline, 4427 (78.1%) had normal LVEF, 602 (10.6%) had mid-range LVEF, and 643 (11.3%) had reduced LVEF. Patients with reduced LVEF were older and had a higher prevalence of smoking, prior MI, and multi-vessel disease. There was a stepwise increase in 3-year event rates moving from normal, to mid-range and reduced LVEF (Figure 1). After multivariable adjustment, hazard ratio (HR) for MACE was 1.45 (95% CI: 1.10–1.92) in patients with mid-range LVEF and 2.43 (95% CI: 1.84–3.22) in patients with reduced LVEF (trend p-value <0.0001). The risk of ST was more than doubled in both mid-range LVEF (HR 2.30, 95% CI: 1.30–4.06, p=0.004) and reduced LVEF patients (HR 2.18, 95% CI: 1.11–4.28, p=0.02), as compared with normal LVEF. Conclusion: The presence of an even mild degree of LVEF impairment confers an increased risk of ischemic events, including ST, among females undergoing PCI with DES. Funding Acknowledgement: Type of funding sources: None.